Immunomodulatory bioactivities of glycomacropeptide - Samuel M. Adler; Matthew R. Paluska; Kimberly R. Svoboda; David C. Dallas (Journal of Functional Foods, 2024)
In cellular models, animal studies, and human feeding studies, glycomacropeptide (GMP) has a range of immunomodulatory bioactivities, including altering cytokine gene expression and production. Direct immunomodulation by GMP is primarily attributed to its interactions with key innate inflammatory pathways, specifically activated B cells (NF-κB) and mitogen-activated protein kinase (MAPK) signaling. Additionally, GMP indirectly modulates immune responses by inhibiting the adhesion of pathogenic bacteria and toxins. Some studies indicate that the sialic acid component of GMP is essential for GMP’s immunoregulatory activity and that GMP can function as a prebiotic. Though some studies incorporate digestion, many studies apply intact GMP directly to cell cultures, limiting the translational significance of these findings toward understanding GMP’s potential as an ingredient in functional foods. This review details GMP’s immunological effects as observed across cellular, animal and human studies, with a particular focus on the modulation of cytokine production and the various mechanisms underlying GMP's immunomodulatory actions.